Assessing Kosovo's horticultural potential: the market for fruit and vegetables on the Balkans - Christian Fischer (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2004)
Kosovo had been a net exporter - at least of some - fruit and vegetables in the former Federal Republic of Yugoslavia before the civil war. Current reconstruction efforts therefore focus on restoring the past horticultural potential of the now independent province. This paper analyses the competitiveness of the Kosovar fruit and vegetable sector. By calculating average net trade flows during 1996-2000 for more than 20 individual fruit and vegetables and seven aggregates, demand potentials for the Balkan regional market are identified for potatoes, lettuce, garlic, dried beans and pears. In addition, average export unit values are calculated as price proxies in order to assess export price competitiveness in the region. While demand potentials for locally produced fruit and vegetables clearly exist, the paper concludes that the overall competitive position of Kosovo's horticultural sector seems rather weak at the moment. – – Vor dem Bürgerkrieg in der ehemaligen Bundesrepublik Jugoslawien war der Kosovo ein Netto-Exporteur von - zumindest einigen - Obst- und Gemüsesorten.Aus diesem Grund kon-zentrieren sich die gegenwärtigen Wiederaufbaubemühungen auf die Wiederherstellung des damaligen gartenbaulichen Potenzials der nun unabhängigen Provinz. Dieses Discussion Paper analysiert die Wettbewerbsfähigkeit des Obst- und Gemüsesektors des Kosovo. Durch die Be-rechnung von 5-Jahres-Durchschnitts-Nettohandelsströmen (1996-2000) von mehr als 20 verschiedenen Obst- und Gemüsesorten und sieben Aggregaten werden Nachfragepotenziale in der Balkanregion für Kartoffeln, Blattsalat, Knoblauch, getrocknete Bohnen und Birnen identifiziert. Darüber hinaus werden durchschnittliche Exporteinheitswerte (Unit Values) als Preisindikatoren berechnet, um die Exportpreis-Wettbewerbsfähigkeit in der Region zu bewerten. Obwohl Nachfragepotenziale nach heimischen Obst- und Gemüseprodukten tat-sächlich nachgewiesen werden können, zeigt die Schlussbetrachtung der vorliegenden Arbeit, dass die Gesamtwettbewerbsfähigkeit des Gartenbausektors im Kosovo gegenwärtig als eher schwach zu beurteilen ist.
urn:nbn:de:gbv:3:2-22297
Keywords: D40; F14; O52; Q00; Q11; Q17; 330; Kosovo; Balkans; horticulture; market analysis; export potential; agriculture in international trade; agricultur and natural resource economies; aggregate supply and demand analysis; price Kosovo; Balkan; Marktanalyse; Nachfragepotential; Internationaler Agrarhandel; Agrar- und Ressourcenökonomie; Analysen des aggregierten Angebots und der aggegrierten Nachfrage; Preise